Highly accurate CCSD(T) and DFT-SAPT stabilization energies of H-bonded and stacked structures of the uracil dimer - Pitoňák, Michal; Riley, Kevin E; Neogrády, Pavel; Hobza, Pavel (ChemPhysChem, 2008)
The CCSD(T) interaction energies for the H-bonded and stacked structures of the uracil dimer are determined at the aug-cc-pVDZ and aug-cc-pVTZ levels. On the basis of these calculations we can construct the CCSD(T) interaction energies at the complete basis set (CBS) limit. The most accurate energies, based either on direct extrapolation of the CCSD(T) correlation energies obtained with the aug-cc-pVDZ and aug-cc-pVTZ basis sets or on the sum of extrapolated MP2 interaction energies (from aug-cc-pVTZ and aug-cc-pVQZ basis sets) and extrapolated DeltaCCSD(T) correction terms [difference between CCSD(T) and MP2 interaction energies] differ only slightly, which demonstrates the reliability and robustness of both techniques. The latter values, which represent new standards for the H-bonding and stacking structures of the uracil dimer, differ from the previously published data for the S22 set by a small amount. This suggests that interaction energies of the S22 set are generated with chemical accuracy. The most accurate CCSD(T)/CBS interaction energies are compared with interaction energies obtained from various computational procedures, namely the SCS-MP2 (SCS: spin-component-scaled), SCS(MI)-MP2 (MI: molecular interaction), MP3, dispersion-augmented DFT (DFT-D), M06-2X, and DFT-SAPT (SAPT: symmetry-adapted perturbation theory) methods. Among these techniques, the best results are obtained with the SCS(MI)-MP2 method. Remarkably good binding energies are also obtained with the DFT-SAPT method. Both DFT techniques tested yield similarly good interaction energies. The large magnitude of the stacking energy for the uracil dimer, compared to that of the benzene dimer, is explained by attractive electrostatic interactions present in the stacked uracil dimer. These interactions force both subsystems to approach each other and the dispersion energy benefits from a shorter intersystem separation.
Keywords: dimerizace; Algorithms; Energy Transfer; Financing, Organized; uracil; Dimerization; Uracil; vodíková vazba; chemické modely; benzen; financování organizované; Hydrogen Bonding; algoritmy; Models, Chemical; přenos energie; Benzene